Numerical simulation of the fouling and cleaning of a ceramic membrane - Rui XIONG; Jia-yu ZHANG; Ming-wei YAN; Guang-chao SUN; Kai-qi LIU (工程科学学报, 2021)
The main sources of fine particulate matter in the air are automobile exhaust and dust-containing hot flue gas emitted from combustion in the process of industrial manufacturing and municipal solid waste incineration, both of which are hard to clean at high temperatures. Ceramic membranes maintain high strength at high temperatures and an acid or alkaline atmosphere, and have a micron-scale and tortuous pores that block dust particles. The ceramic membrane is one of the most effective materials for successful hot flue gas cleaning as used in the integrated gasification combined cycle. Its filtration and regeneration performance are related to the deposition and desorption mechanism of dust particles in the channel of the membrane. In this study, a physical model of ceramic membranes of various porosities was established. Boundary and deposition conditions were then set up by combining continuity, momentum, and energy equations to simulate the flow of hot flue gas and the deposition and desorption process of dust particles during ceramic membrane filtration and pulse back-blowing. The results show that when the filtration velocity is low and porosity of the ceramic membrane is high, it is easy for dust particles to deposit in the membrane channel. Increasing back-blowing pressure prolongs back-blowing time during pulse back-blowing so that dust particles easily desorb from the channel of the ceramic membrane. When a ceramic membrane tube with a thickness of 20 mm, a length of 1.5 m, and a porosity of 40% is used to filtrate flue gas with a filtration temperature of 1000 °C, a flow rate of 1 m·min−1, and a pressure of 0.1 MPa, the blowback pressure should not be <0.3 MPa, blowback time should be longer than 0.02 s, and pulse blowback time interval should be more than 452 s.